Ultra-Micro Financing Literacy for KSBI MSME Entrepreneurs - Dini Hariyanti; Osni Erza; Khairunnisa (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting Indonesia’s national economy. However, one of the major challenges for MSMEs—especially ultra-micro businesses—is their low level of financial literacy, which limits access to formal financing. This community service program aims to increase ultra-micro financing literacy among members of Komunitas Sukses Berjamaah Indonesia (KSBI). The program applied a community-based empowerment approach using Participatory Action Research (PAR) and involved 20 ultra-micro entrepreneurs in South Jakarta. Activities included initial observation, Focus Group Discussions, financial literacy training, financing application simulations, technical mentoring, and evaluation through pre-test and post-test. The results showed an increase in participants’ understanding from an average of 41.4% to 60.2%, reflecting a 45% improvement. Beyond knowledge gains, the program also facilitated the formation of a community financial literacy team and the emergence of local leaders who play a key role in ensuring program sustainability. These findings demonstrate that community-based financial literacy education can effectively expand access to formal financing for ultra-micro enterprises. Replicating similar programs in other communities has strong potential to strengthen economic independence and promote financial inclusion.